Informasi Penyebaran Penyakit AIDS Berbantuan Web Gis Di Wilayah Pati (Information Technology and Telematics, 2015)
ABSTRACT Acquired Immunodeficiency Syndrome (AIDS) is a collection of symptoms and infections (syndrome) resulting from the destruction of the human immune system caused by HIV infection. Name virus  Human Immunodeficiency Virus / HIV is the virus that weakens the immunity in the human body. People affected by this virus will be susceptible to opportunistic infections or tumors susceptible. The purpose of this system is built is to assist and facilitate the institution that is related namely Pati District Health Office to map and outreach within the community. This system gives information in the form of charts and spread in the form of Web GIS. Keywoard: spread of diseas, AIDS , Web GIS.